SCAFFOLDING AS A WAY TO DIFFERENTIATE LANGUAGE INSTRUCTIONS - AGulrukh Nabiyevna Yusupova (Western European Studies, 2025)
This paper explores scaffolding as an effective approach to differentiate instruction in language education. It examines the theoretical foundations of scaffolding based on Vygotsky’s Zone of Proximal Development and integrates findings from recent studies to highlight its relevance in contemporary classrooms. The discussion transitions from theory to practice by presenting design strategies and practical implications for implementing scaffolding to support diverse learners. The paper emphasizes how calibrated assistance and gradual release of responsibility can enhance language acquisition, promote learner autonomy, and make challenging content accessible to all students
Keywords: instructional approach; differentiation; scaffolding